Clinical Nurse Specialist: a model of advanced nursing practice in pediatric oncology in Brazil - Dias, Carla goncalves (2013)
The objective of this paper is to report the experience of implementing a model of advanced nursing practice that integrates a clinical nurse specialist into the nursing staff. The authors describe the concept of this model and the process of its implementation in a pediatric oncology reference institution in the city of São Paulo, Brazil. The main result achieved in evaluating the clinical nurse specialist was strengthening of the role of the nurse as a reference professional for the articulation of the various demands of care in assisting the child, adolescent or young adult with cancer and his/her family. The satisfaction of these users due to the closer relationship between the patient, family and clinical nurse in all stages of the caring process also stands out.